Faktor-Faktor yang Mempengaruhi Motivasi Menabung Mahasiswa Menggunakan Path Analysis: (Studi Kasus : Mahasiswa Pendidikan Agama Islam Universitas KH. A Wahab Hasbullah Tambakberas) - Wardani, Dian Kusuma (Exact Papers in Compilation (EPiC), 2020)
Path Analysis was developed by Sewall Wright in 1934 which aims to explain the direct and indirect effects of a set of causal variables (exogenous variables) on a set of effect variables (endogenous variables). Primary data is used in this study. The population is 421 students of the Islamic Religious Education study program at KH A Wahab Hasbullah University. The sampling technique used is simple random sampling, and from the calculation results obtained 75 samples taken from the population. The analysis method used in this study uses path analysis. The purpose of this study was to determine the structural relationship between exogenous variables (parent motivation, lecturer motivation, student's personal needs and savings program in campus) to endogenous variables (student understanding of money and saving and saving motivation). The results showed that the Y2 variable (students' interest in saving ) had a direct or indirect influence from the variables X1 (parents) and X2 (lecturers). Whereas the variables X3 (student university needs) and X4 (saving program in campus) have a direct effect